Mechanosensation Mediates Long‐Range Spatial Decision‐Making in an Aneural Organism (Adv. Mater. 34/2021). Issue 34 (24th August 2021) - Murugan, Nirosha J.; Kaltman, Daniel H.; Jin, Paul H.; Chien, Melanie; Martinez, Ramses; Nguyen, Cuong Q.; Kane, Anna; Novak, Richard; Ingber, Donald E.; Levin, Michael
Abstract : Biomechanical Signaling Physarum polycephalum, a slime mold with one cell and no brain, is a remarkable new model for understanding basal cognition. Its living material deforms its own structure to interact with the objects around it. In article number 2008161, Michael Levin and co‐workers show that Physarum senses strain in its substrate, using biomechanical signaling to assess the environment and express its preferences as directional growth decisions.